Effective Strategies to Promote the Cultivation of Public Legal Consciousness from the Perspective of Social Psychology. (3rd October 2022) - Yi, Liang; Li, Tianxia
Abstract : In order to build a harmonious economic society, show the legal function in the society, enable people to live and work in a better environment, and increase people's practicality in the legal society, it needs to be analyzed from the perspective of social psychology. This paper comprehensively analyzes the current public legal knowledge, uses a deep neural network model, and implements the cultivation of public legal awareness. On this basis, it integrates the data and information before and after 2020, uses the method of book case distribution training, constructs a legal framework, relies on the data distribution technology, constructs a web legal awareness training system, and increases the conditions for promoting the cultivation of public legal awareness based on the background operation of the integrated website. It can be seen that in the perspective of social psychology, the importance of the cultivation of public legal awareness can be achieved through new algorithms, so that people can pay attention to the cultivation of legal awareness, which can provide corresponding protection for the operation and maintenance of the legal system.